A light-driven Nernstian biosupercapacitor. (20th May 2019) - Zhao, Fangyuan; Bobrowski, Tim; Ruff, Adrian; Hartmann, Volker; Nowaczyk, Marc M.; Rögner, Matthias; Conzuelo, Felipe; Schuhmann, Wolfgang
Abstract: Following inspiration by natural photosynthesis, the design and fabrication of semi-artificial biophotoelectrochemical devices able to harvest solar energy and aiming on the implementation of green and sustainable energy conversion systems is presently an important field of research. Here we present the development of a fully light-driven biosupercapacitor fabricated by incorporation of isolated photosystem 2 and photosystem 1 protein complexes embedded within the same Os-complex modified redox polymer. By this, light energy is stored at both electrodes within the polymer-based pseudocapacitive matrix in the form of Os 3+ centers at the photosystem1-based biocathode and in the form of Os 2+ centers at the photosystem 2-based bioanode. The stored energy can be released on demand into bursts of electricity. Due to the purely light-driven self-charging process, the biosupercapacitor provided a power output of 1.0 μW cm −2 after 200 s charging time. Moreover, the use of different electrode materials and their implication on the performance of the implemented biodevice is evaluated. Graphical abstract: Image 1